Tourism policy development: a Malaysian experience - Awang, Khairil Wahidin; Abdul Aziz, Yuhanis (Penerbit Universiti Teknologi MARA (UiTM) Malaysia, 2010)
This paper has the objective of tracing the historical development of tourism policies in Malaysia, an underpinning factor towards understanding the full potential of tourism as an industry in the country. It begins with the justification of using tourism as the agent of change, in the drive towards multiplying the economic base of the country. It ends with the highlighting of contemporary practice of tourism, with a notion to further strengthen established industry foothold. Secondary data, together with complementary data from in-depth interviews with policy makers formed the basis of the arguments. Findings suggest that tourism is viewed as a very important industry as emphasized by respective policies. Findings suggest too that although there are bounds of success, with regard to tourism development in Malaysia, the political-administration system, which is based on the federal constitution also, has some drawbacks. For one, a bottom-up planning in-put would be ideal. In parallel, planning and developing of tourism has to be dynamic due to the ever changing surroundings.